The total social cost evaluation of two wind and PV energy development modes: A study on Henan of China. (November 2021) - Sun, Bing; Li, Yunfei; Zeng, Yuan; Yang, Tiankai; Dong, Shimeng
Abstract: In Henan province of China, the power demand is vigorous, and the existing provincial generators are mostly high-carbon. Henan faces greater challenges in electricity revolution than other provinces. Currently, there are two development modes for generating low-carbon electricity in Henan: the "large-scale and long-distance transmission" (LSLDT) mode and the "local development and consumption" (LDC) mode. To make a better choice on development mode, following works have been done. Firstly, as there is still no macro evaluation on the self-sufficiency ratio by photovoltaic (PV) power in each region of Henan, a rooftop PV installation potential evaluation method based on the roof covering rate is proposed. And two development scenes for wind and PV power generation are set to fit the development trend of Henan in the near future. Secondly, as the load can only be stably supplied by the cooperation of wind turbine, PV equipment and other controllable generation, the real cost of wind turbine and PV power generation is never only the equipment investment. Different from the commonly used levelized cost of electricity method, a bi-level generation planning model based on the total social cost is established. Finally, generation planning schemes are made and the power supply cost per kWh electricity is evaluated under the two development scenes mentioned above. It is found that there is a significant cost advantage when wind and PV electricity are generated with the LDC mode in both scenes. What is more, the existence of reliability cost, wheeling cost and grid-loss cost makes the LSLDT mode difficult to cut down the wind and PV power supply cost. Wind and PV power generation of the LDC mode should be focused on in Henan. Highlights: The local development and consumption mode could supply cheaper wind and PV electricity in Henan. Based on total social cost estimation, the LSLDT mode can't supply cheaper power even with better renewable resources. The LDC mode should be focused on for low-carbon wind and PV power generation in Henan Province. Rooftop PV is with the potential meeting more than 40% of prospective electricity demand in Henan of China.